Unmasking the Role of Uptake Transporters for Digoxin Uptake Across the Barriers of the Central Nervous System in Rat. (9th March 2017) - Taskar, Kunal S; Mariappan, T Thanga; Kurawattimath, Vishwanath; Singh Gautam, Shashyendra; Radhakrishna Mullapudi, TV; Sridhar, Srikanth K; Kallem, Raja Reddy; Marathe, Punit; Mandlekar, Sandhya
The role of uptake transporter (organic anion–transporting polypeptide [Oatp]) in the disposition of a P-glycoprotein (P-gp) substrate (digoxin) at the barriers of central nervous system, namely, the blood-brain barrier (BBB), blood-spinal cord barrier (BSCB), and brain-cerebrospinal fluid barrier (BCSFB), was studied using rat as a preclinical species. In vivo chemical inhibition of P-gp and Oatp was achieved using elacridar and rifampicin, respectively. Our findings show that (1) digoxin had a low brain-to-plasma concentration ratio (B/P) (0.07) in rat; (2) in the presence of elacridar, the B/P of digoxin increased by about 12-fold; (3) rifampicin administration alone did not change the digoxin B/P significantly when compared with digoxin B/P alone; (4) rifampicin administration along with elacridar resulted only in 6-fold increase in the B/P of digoxin; (5) similar fold changes and trends were seen with the spinal cord-to-plasma concentration ratio of digoxin, indicating the similarity between BBB and the BSCB; and (6) unlike BBB and BSCB, the presence of rifampicin further increased the cerebrospinal fluid-to-plasma concentration ratio (CSF/P) for digoxin, suggesting a differential orientation of the uptake transporters at the BCSFB (CSF to blood) compared with the BBB (blood to brain). The observations for digoxin uptake, at least at the BBB and the BSCB, advocate the importance of uptake transporters (Oatps). However, the activity of such uptake transporters became evident only after inhibition of the efflux transporter (P-gp).